ESTETIC EXPRESSIONS OF JEPARA CARVING IN EFFORTS TO DEAL WITH THE MARKET DEMANDS - Muhajirin Muhajirin (Corak : Jurnal Seni Kriya, 2019)
The demands of consumers that always evolving makes Jepara craftsmen have to adjust themselves. This is reflected in the aesthetic expression of products that are no longer homogeneous. The purpose of this paper is to analyze the aesthetic expression of Jepara carving art in an effort to face global challenges. Data obtained through interviews and direct observation in the field. The results of the study show that the carving that has now undergone a change due to adjusting to the demands of consumers and the times. European market dominance influenced European-style furniture so that the expression of Jepara carving tends to be European. However, it also developed a carving motif not fixated on the usual themes that were made in the form of motifs with stylized forms of flora fauna, but now also developed geometric and minimalist designs. There is also a simplification of a form into another form, such as by simplifying carving motifs to serve consumers who want products that are not too full of carvings. This consumer demand motivates craftsmen to always do innovation, so consumers are accommodated and served the satisfaction of their aesthetic taste and craftsmen fulfilled their economic needs. Keywords: Aesthetic expression, Jepara carving, market demands